Tembang Dolanan Anak-anak - Sri Hesti Heriwati (Institut Seni Indonesia Surakarta, 2007)
consciouslY makes every effort to express the sense. One can find an outlet for his estbetic sense through various kinds of means or media. A literary man will express his estbetic sense through a means of language. A language is something that is not separable from human lift. Children understand the realz!J around them, make social interaction and describe the reality again using a language. Tembang dolanan. a work of art with which children familiar, is an author's work containing estbetic values.A literary text is a whole systemic unit of language taken the shape of oral or writing utterance. A text specifically refers to a unit syntacti« or semantic strudllre which coherentlY creates interrelated relations so it makes a full message/ injormation. A literary text contained in children bembang dolanan is possible to be anaIYzed from ma'!Y aspects depending on the study. In relation to the above problems, the discourse of children's tembang dolanan will be closelY studied grammaticallY and lexicallY.Keywords: Tembang (recited Javanese Poetry), discourse, grammatical, lexical.